FPYM: development and application of a fuzzy-based Poka-Yoke model for the improvement of software performance. (2017) - Baseer, K.K.; Reddy, A. Rama Mohan; Bindu, C. Shoba
Improving qualities of software like reliability, availability, maintainability, cost, time and energy is key role in software development. These qualities are more dependable on the requirements, design, development, testing and deployment. In order to improve the software qualities on these cycles, avoiding mistakes or making alarm for each activity may be suitable choice. This is effectively studied using Poka-Yoke model which is applied in various production, manufacturing and software industries. Due to advantages of Poka-Yoke model, we have developed fuzzy-based Poka-Yoke model for small-scale software companies. This work aims to study the workflow and activities of two small scale companies involved in software development. In the case study, software performance attributes are defined and performance is analysed using four metrics called, UGAM, IOI, SM and SSM. The collected data is then extensively analysed to identify: the individual characteristics of companies, correlation behaviour of companies which they implemented the proposed model, improvement analysis over the period of time with the proposed model and forecasting the software performance for next products.